Cryptanalysis Knapsack Cipher Using Artificial Immune System - Eman Al-Obaidy (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this work, the use of an artificial immune system (AIS ) in  cryptanalysis  is explored. This AIS uses the clonal selection principle for the cryptanalysis of knapsack cipher. Results showed that the proposed approach is good especially when the effect of the control parameters on the performance of the clonal selection  is well taken into consideration.  The program is written  in Turbo C.